Principle and calculation method of hydraulic fracturing technique for in-situ stress based on two arbitrary holes - Hailong Dong; Wei Jing; Jun’ai Luo; Zhengxin Zhang; Laiwang Jing; Wenli Zhang; Zhen Lei (Scientific Reports)
Abstract In order to precisely obtain the magnitude and orientation of in-situ stress in coal mine roadway, the principle and calculation method of hydraulic fracturing technique for in-situ stress with two arbitrary holes were established in this study. Deriving from the basic principle of the traditional hydraulic fracturing in-situ stress testing, this method, based on the basic data of in-situ stress measured from two arbitrary test holes, performed three stress equivalent transformations following the stress transformation formula in elasticity mechanics. The results suggest that all six stress values representing the stress state at a point were accurately obtained after mechanical and mathematical derivation. Furthermore, the practical application and in-situ stress calculation process of this method were introduced with the Nazuo Coal Mine in Fuyuan County, Yunnan Province of China as the engineering foundation, verifying that the testing results were relatively accurate. The proposed method has addressed the limitations of the traditional single-hole hydraulic fracturing method and mitigated the drawbacks of the three-hole hydraulic fracturing method, what is high requirements for drilling quality and is not practical. So it can be treated as a simple, accurate method for hydraulic fracturing in-situ stress testing.